1991
DOI: 10.1002/jgt.3190150304
|View full text |Cite
|
Sign up to set email alerts
|

Regular factors in K1,3‐free graphs

Abstract: We show that every connected Kl,sfree graph with minimum degree at least 2k contains a k-factor and construct connected K1,3-free graphs with minimum degree k + O(dk) that have no k-factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Results of both Choudum & Paulraj [2] and Egawa & Ota [4] imply that a moderate minimum degree condition already guarantees that a claw-free graph contains a 2-factor.…”
Section: Known Resultsmentioning
confidence: 95%
“…Results of both Choudum & Paulraj [2] and Egawa & Ota [4] imply that a moderate minimum degree condition already guarantees that a claw-free graph contains a 2-factor.…”
Section: Known Resultsmentioning
confidence: 95%
“…It follows from either [2] or [3] that every claw-free graph G with δ(G) 4 has a 2-factor. Yoshimoto [9] showed that a claw-free graph G with δ(G) 3 has also a 2-factor if, additionally, G is 2-connected.…”
Section: Gould and Hynds Inmentioning
confidence: 99%
“…[8], Lai, Li, Shao and Xiong [7]) Let G be a clawfree graph. If G has a connected even factor H, then G has a connected even [2,4]…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…From the results of Choudum and Paulraj [2], and Egawa and Ota [3], one can deduce that every claw-free graph with minimum degree at least 4 has a 2-factor. Very recently, Yoshimoto show that the minimum degree can be reduced if we increase its connectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation